Hydrogen peroxide constricts rat arteries by activating Na+-permeable and Ca2+-permeable cation channels. (2nd January 2019) - Park, Hyun Ji; Shin, Kyung Chul; Yoou, Soon-Kyu; Kang, Myeongsin; Kim, Jae Gon; Sung, Dong Jun; Yu, Wonjong; Lee, Youngjin; Kim, Sung Hea; Bae, Young Min; Park, Sang Woong
Abstract: Oxidative stress is associated with many cardiovascular diseases, such as hypertension and arteriosclerosis. Oxidative stress reportedly activates the L-type voltage-gated calcium channel (VDCCL ) and elevates [Ca 2+ ]i in many cells. However, how oxidative stress activates VDCCL under clinical setting and the consequence for arteries are unclear. Here, we examined the hypothesis that hydrogen peroxide (H2 O2 ) regulates membrane potential (Em) by altering Na + influx through cation channels, which consequently activates VDCCL to induce vasoconstriction in rat mesenteric arteries. To measure the tone of the endothelium-denuded arteries, a conventional isometric organ chamber was used. Membrane currents and Em were recorded by the patch-clamp technique. [Ca 2+ ]i and [Na + ]i were measured with microfluorometry using Fura2-AM and SBFI-AM, respectively. We found that H2 O2 (10 and 100 µM) increased arterial contraction, and nifedipine blocked the effects of H2 O2 on isometric contraction. H2 O2 increased [Ca 2+ ]i as well as [Na + ]i, and depolarised Em. Gd 3+ (1 µM) blocked all these H2 O2 -induced effects including Em depolarisation and increases in [Ca 2+ ]i and [Na + ]i . Although both nifedipine (30 nM) and low Na + bath solution completely prevented the H2 O2 -induced increase in [Na + ], they only partly inhibited the H2 O2 -induced effects on [Ca 2+ ]i and Em. Taken together, the results suggested that H2 O2 constricts rat arteries by causing Em depolarisation and VDCCL activation through activating Gd 3+ -and nifedipine-sensitive, Na + -permeable channels as well as Gd 3+ -sensitive Ca 2+ -permeable cation channels. We suggest that unidentified Na + -permeable cation channels as well as Ca 2+ -permeable cation channels may function as important mediators for oxidative stress-induced vascular dysfunction.